The Impingement Flow Study on the Temperature Profile Perforated Plate - Wong, Wei Cong (Universiti Sains Malaysia, 2021)
Thermal anti-ice system is one type of anti-icing system that provided sufficient heat energy to cause the supercooled water that impinge on the aircraft surface to evaporate. The hotspot temperature profile on the perforated plate is concerned as the hot air temperature might destroy the Bias Acoustic Liner that applied on the nacelle lip, since Bias Acoustic Liner surface is fabricated by thin aluminium plate. In this paper, the effect of Reynolds number and the hole arrangement to the temperature distribution of the perforated plate are studied for a hot impingement jet. Geometrical models that consist of a nozzle inlet, air domain and different hole arrangement of perforated plate are created and 70°C hot air jet is impinged on the perforated plate through the nozzle inlet. It can be observed that the dimensionless temperature will be increased when the Reynolds number of the flow increased. The increment of the dimensionless temperature increased from 0.02 to 0.04 when the flow increased from low Reynolds number to high Reynolds number. For the effect of hole arrangement on the temperature distribution of perforated plate, the dimensionless temperature of hole arrangement without centre hole is 0.25 higher than the hole arrangement with centre hole under high Reynolds number flow. In terms of the pattern of hole arrangement, it has been shown that dimensionless temperature for the 3 cm tandem hole arrangement is 0.04 higher than the 4cm staggered hole arrangement under high Reynolds number flow. Tandem arrangement without centre hole is recommended for Bias acoustic Liner as a thicker high temperature layer will be developed at the outer surface and the dimensionless temperature for the plate is considerably high.